The Effect Of Hypnobirthing On The Anxiety Level Of Pregnant Women In Trimester III - Khairunnisa Situmorang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Every pregnant woman will experience physical and psychological changes that can trigger anxiety in the mother. Anxiety that occurs in third trimester pregnant women if not handled properly can have a negative impact on both the mother and the fetus. Hypnobirthing is a technique that can reduce anxiety in pregnant women. This study aims to determine the effect of hypnobirthing on the anxiety level of pregnant women in the third trimester in the work area of the Romana Clinic. This type of research is Quasy Experimental with a pretest and posttest control group design. This research was conducted at the Romana Clinic. A sample of 30 pregnant women in the third trimester who met the inclusion criteria using the accidental sampling method, the independent variable of this study was hypnobirthing and the dependent variable was the level of anxiety of pregnant women in the third trimester and used the HARS questionnaire as an anxiety measure. The data analysis technique used the Wilcoxon test with the SPSS program. From the results of the Wilcoxon test, all pregnant women experienced a decrease in anxiety after being given treatment in the form of Hypnobirthing with a p value of 0.01 smaller than 0.05 so it was said that there was an effect of Hypnobirthing on the anxiety level of third trimester pregnant women.